Inferior mesenteric vein thrombophlebitis secondary to acute diverticulitis - Andrew Waack, BS; Akash Ranabothu; Avish Persaud, BS; Meghana Ranabothu, BS; Venkatramana Vattipally, MD (Radiology Case Reports, 2023)
Inferior mesenteric vein thrombophlebitis is an uncommon condition. Most cases of portal-mesenteric thrombophlebitis affect either the portal vein or superior mesenteric vein; it is not known why the inferior mesenteric vein is less affected. Thrombophlebitis typically occurs following inflammatory intra-abdominal processes, such as diverticulitis. Diverticulitis is a common condition in the Western world, with several common complications, such as fistula formation and bowel wall perforation. However, although diverticulitis is a common cause of portal-mesenteric thrombophlebitis, thrombophlebitis is still a rare complication of diverticulitis. We present a case of diverticulitis complicated with interior mesenteric vein thrombophlebitis with gas extension into the portal vein.